THE TRANSLATION QUALITY OF SENIOR HIGH SCHOOL STUDENTS IN TRANSLATING NARRATIVE TEXT - Khairiyah, Nabila Ananda; Abduh, Amirullah; Tahir, Muh. (Universitas Negeri Makassar, 2023)
This study aims to determine the quality of the translation of high school students in translating narrative texts. The researcher used a mixed method triangulation research method (quantitative-qualitative). To achieve the research objectives, the data collected is the result of tests and interviews. The subjects of this study were 28 students of class IX of SMAN 6 Maros in class IX of Cross Interests in English. The interviews were given to 7 students who produced high and medium translation quality. The results of this study indicate that the translation quality of students is of very low quality with an average value of 47.46. Only 5 of 28 students produced high-quality translations with a percentage of 100%, 2 of 28 students produced medium-quality translations with a percentage of 68% and 21 of 28 students produced very low-quality translations with a percentage of 33%. Based on the interview results, it can be concluded that 4 factors caused 7 students to produce high and medium-quality translations. The four factors are; a. The factor of interest in English so that it has a lot of known English vocabulary; b. From the habit factor, in this case, the average student likes to listen to English songs and watch films from abroad that use English; c. Some students have studied English outside of school hours so that the student's English proficiency is higher than other students; d. The narrative text that the researcher uses for the test is a text that is very familiar among students because the text is adapted from cardboard films which are liked by almost all people.